2022
DOI: 10.1021/acsomega.2c05505
|View full text |Cite
|
Sign up to set email alerts
|

IQ Motif Containing GTPase Activating Proteins (IQGAPs), A-Kinase Anchoring Proteins (AKAPs) and Kinase Suppressor of Ras Proteins (KSRs) in Scaffolding Oncogenic Pathways and Their Therapeutic Potential

Abstract: Scaffolding proteins colocalize interacting partners on their surface and facilitate complex formation. They have multiple domains and motifs, which provide binding sites for various molecules. This property of scaffolding proteins helps in the orderly transduction of signals. Abnormal signal transduction is frequently observed in cancers, which can also be attributed to the altered functionality of scaffolding proteins. IQ motif containing GTPase activating proteins (IQGAPs), kinase suppressor of Ras (KSR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…SLiMs have emerged as a ubiquitous modules in the organization of protein-protein interaction networks. For example, SLiMs designate substrates for post-translational modification including kinases and phosphatases, target cellular localization, and control docking to adaptors, assembly of signaling complexes, and recruitment of enzymes to multi-protein complexes (Manna et al, 2018;Mohapatra and Dixit, 2022;Peti and Page, 2013;Ragusa et al, 2010;Shi et al, 2023;Sorgeloos et al, 2022;Srivastava et al, 2023;Wang et al, 2016). The number of eukaryotic SLiM classes is in the hundreds and rapidly expanding, and it has been estimated there may be more than a hundred thousand of instances of such motifs in the human proteome (Davey et al, 2023;Kumar et al, 2022;Tompa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SLiMs have emerged as a ubiquitous modules in the organization of protein-protein interaction networks. For example, SLiMs designate substrates for post-translational modification including kinases and phosphatases, target cellular localization, and control docking to adaptors, assembly of signaling complexes, and recruitment of enzymes to multi-protein complexes (Manna et al, 2018;Mohapatra and Dixit, 2022;Peti and Page, 2013;Ragusa et al, 2010;Shi et al, 2023;Sorgeloos et al, 2022;Srivastava et al, 2023;Wang et al, 2016). The number of eukaryotic SLiM classes is in the hundreds and rapidly expanding, and it has been estimated there may be more than a hundred thousand of instances of such motifs in the human proteome (Davey et al, 2023;Kumar et al, 2022;Tompa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for g protein-coupled receptors, AKAPs serve as a central hub in tissues for G protein-coupled receptors, allowing for the assembly of multiple protein kinases and phosphatases to create signal devices able to send signals, regulate and transport within cells [ 21 , 22 ]. It has been proved that AKAPs are pivotal for the initiation / progression of tumors and serve as potential targets of drug therapy [ 7 , 23 ]. For example, Zhang et al confirmed that AKAP4 was up-regulated in the tissues of non-small cell lung cancer, and the knockdown of AKAP4 inhibited tumor growth as well as epithelial-mesenchymal transformation, suggesting that AKAP4 might be a pivotal target in treating this disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway or mitogen‐activated protein kinase pathway [14] represents a cascade of protein kinases that are considered a key signaling pathway for the regulation of cellular and molecular functions like proliferation, apoptosis, differentiation and stress response [15]. The emergence of the MAPK pathway stems back 30 years ago [16] and is grouped into three families in mammals, namely, extracellular signal regulated kinases (ERKs), p38/SAKs, and c‐Jun N‐terminal kinases (JNKs) [17].…”
Section: Cell‐intrinsic Pathways Involved In Cancer Cell Plasticitymentioning
confidence: 99%